Effect Of Student Learning Motivation And Lecturer Competence On Student Achievement In Commerce Correspondence Learning - Sudarjo, Sudarjo; Suyitno, Suyitno (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This study aims to analyze whether there is a significant influence between lecturer competence from a student's point of view and learning motivation on student learning achievement in the Commerce Correspondence subject, Office Management Departement, STIE Indonesia Malang. The research data were collected using a questionnaire from 85 respondents, then analyzed using Multiple Linear Regression with the help of the SPSS version 25 computer application. The results showed that the variable student learning motivation partially had a positive and significant effect on student achievement as evidenced by a tcount of 4,572 or more greater than ttable (2.048) with a significant level of 0.000. The lecturer competency variable also partially shows a positive and significant effect on student learning achievement as evidenced by the tcount value of 3.358 which is greater than ttable (2.048) with a significant level of 0.002. Simultaneously, student learning motivation and lecturer competence have a positive and significant effect on student achievement as evidenced by the Fcount value of 16.319 greater than Ftable (3.30) with a significant level of 0.000.